Combining local cytokine delivery and systemic immunization with recombinant artLCMV boosts antitumor efficacy in several preclinical tumor models - Kimberly Pojar; Diana Reckendorfer; Judith Strauss; Sarah Szaffich; Sarah Ahmadi-Erber; Timo Schippers; Pedro Berraondo; Klaus K. Orlinger; Josipa Raguz; Henning Lauterbach (OncoImmunology)
Among the plethora of cancer immune evasion mechanisms, T-cell-inhibiting factors within the tumor microenvironment impose a major challenge for the development of novel immunotherapies. Strategies to overcome immunosuppression and remodel the TME are therefore urgently needed. Therapeutic cancer vaccines based on engineered arenaviruses have been proven to generate potent tumor specific CD8+ T-cell responses in preclinical models and cancer patients. Despite signs of clinical activity as monotherapy, combination therapies are needed to further increase the therapeutic effect. To address this need, we evaluated the efficacy of recombinant vectors based on lymphocytic choriomeningitis virus encoding the T-cell stimulating cytokines IL-7, IL-12 and IL-15 with or without tumor-associated antigens. These vectors were tested in three different mouse tumor models (TC-1, MC-38 and B16.F10). Our results demonstrate that only IL-12 encoding vectors led to increased immunogenicity and efficacy, which, after systemic administration, was associated with adverse events. The safest and most potent regimen consisted of systemic vaccination with tumor antigen encoding vectors and local injection of IL-12-encoding vectors. A single round of this treatment regimen resulted in 86–100% tumor-free mice and warrants further investigation.